Effects of Anthocyanins on Vascular Health - Ioana Mozos; Corina Flangea; Daliborca C. Vlad; Cristina Gug; Costin Mozos; Dana Stoian; Constantin T. Luca; Jarosław O. Horbańczuk; Olaf K. Horbańczuk; Atanas G. Atanasov (Biomolecules, 2021)
Cardiovascular disorders are leading mortality causes worldwide, often with a latent evolution. Vascular health depends on endothelial function, arterial stiffness, and the presence of atherosclerotic plaques. Preventive medicine deserves special attention, focusing on modifiable cardiovascular risk factors, including diet. A diet rich in fruits and vegetables has well-known health benefits, especially due to its polyphenolic components. Anthocyanins, water-soluble flavonoid species, responsible for the red-blue color in plants and commonly found in berries, exert favorable effects on the endothelial function, oxidative stress, inhibit COX-1, and COX-2 enzymes, exert antiatherogenic, antihypertensive, antiglycation, antithrombotic, and anti-inflammatory activity, ameliorate dyslipidemia and arterial stiffness. The present review aims to give a current overview of the mechanisms involved in the vascular protective effect of anthocyanins from the human diet, considering epidemiological data, in vitro and in vivo preclinical research, clinical observational, retrospective, intervention and randomized studies, dietary and biomarker studies, and discussing preventive benefits of anthocyanins and future research directions.